Documents from Swakara Board Archive in Windhoek (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2020)
RDF file containing bibliographical references of Swakara archive in Windhoek.
Keywords: Archival materials; Apartheid; Colonisation; German Colonialism; Namibia; Germany